Fostering AI literacy: A teaching practice reflection - Pretorius, Lynette (Journal of Academic Language and Learning, 2023)
This paper provides the reflections of an educator regarding the pedagogical use of generative artificial intelligence and the need for students to develop artificial intelligence literacy. It starts by providing an overview of generative artificial intelligence and the controversy that surrounds the technology in the contemporary higher education context. This is followed by an argument highlighting that the controversy in the field ignores the pedagogical applications of generative artificial intelligence. Finally, this paper demonstrates an example of how generative artificial intelligence has been used as part of a teaching strategy to help research students develop their artificial intelligence literacy. The paper argues that explicit modelling by educators can help students develop an understanding of generative artificial intelligence as a tool to improve their learning.